2015
DOI: 10.1097/mib.0000000000000486
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Desmoglein 2 Contributes to the Pathogenesis of Crohnʼs Disease

Abstract: We show an important role of p38MAPK-mediated regulation of desmosomal adhesion resulting in upregulation of claudin-2 in CD. Our data suggest peptide-mediated strengthening of impaired Dsg2 adhesion as a novel therapeutic approach in CD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
77
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 41 publications
(85 citation statements)
references
References 42 publications
8
77
0
Order By: Relevance
“…However, in the course of several hours treatment with anisomycin impaired barrier function also. This is in line with our previous data, as treatment with TNFα activated p38MAPK which resulted in loss of cell cohesion and increased permeability as well as reduction of Dsg2 at the cell borders 19 .…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…However, in the course of several hours treatment with anisomycin impaired barrier function also. This is in line with our previous data, as treatment with TNFα activated p38MAPK which resulted in loss of cell cohesion and increased permeability as well as reduction of Dsg2 at the cell borders 19 .…”
Section: Discussionsupporting
confidence: 93%
“…Both, an antibody directed against Dsg2 as well as siRNA-mediated Dsg2 depletion resulted in loss of cell cohesion and reduced barrier function 12, 19, 22 . Since Dsg2 was missing at cell junctions in patients suffering from CD and a Dsg-specific tandem peptide ameliorated barrier dysfunction in response to TNF-α, which is regarded as a central cytokine in CD pathogenesis, we concluded that impaired Dsg2 may contribute to pathogenesis of inflammatory bowel diseases (IBD) 19 . This is supported by the finding that cytokines in IBD via matrix metalloproteinase 9 (MMP9) and a disintegrin and metalloproteinase domain-containing protein 10 (ADAM10) cause ectodomain cleavage of Dsg2, the products of which further compromised barrier integrity 18 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This was shown to be mediated by the p38 MAPK pathway due to a significant dephosphorylation of p38 MAPK after the application of GDNF in vitro (36). The latter mechanism has been previously shown to stabilize the intestinal epithelial barrier (51). Additionally, GDNF induced a cAMP/PKA-dependent increase of proliferation and augmented epithelial wound healing.…”
Section: Gdnf Directly Promotes Barrier Maturation and Proliferation mentioning
confidence: 87%
“…Decreased expression of AJ and TJ proteins is not the only mechanism that underlies functional defects of epithelial junctions in the inflamed intestinal mucosa, where junctional proteins are frequently redistributed from the cell-cell contact into cytoplasmic compartments [25, 94, 95]. Vesicle trafficking plays a key role in the establishment and remodeling of epithelial junctions at the plasma membrane.…”
Section: Altered Trafficking Of Aj/tj Proteins In the Inflamed Gutmentioning
confidence: 99%